2010
DOI: 10.1007/s00421-010-1476-9
|View full text |Cite|
|
Sign up to set email alerts
|

Load-dependent movement regulation of lateral stretch shortening cycle jumps

Abstract: The classical stretch shortening cycle (SSC) describes sagittal joint flexion-extensions in motions like running or hopping. However, lateral movements are integral components of team sports and are associated with frontal plane joint displacements. The purpose of this study is to identify neuromuscular and kinematical mechanisms determining motor control and performance of reactive laterally conducted SSCs. Lateral jumps were performed from four distances in order to investigate the influence of lateral stret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 54 publications
3
52
0
Order By: Relevance
“…Fleischmann et al [35] found no differences in angular displacement at the ankle joint during landing jumps at different distances, so for now we could consider that submaximal jumps may well have revealed the same group effects, yet this still needs to be seen. Furthermore, given the exploratory nature of the current study, the alpha level in the SPM analyses was not corrected for the dependent planes of joint motion, as in a previous paper [17].…”
Section: Discussionmentioning
confidence: 80%
“…Fleischmann et al [35] found no differences in angular displacement at the ankle joint during landing jumps at different distances, so for now we could consider that submaximal jumps may well have revealed the same group effects, yet this still needs to be seen. Furthermore, given the exploratory nature of the current study, the alpha level in the SPM analyses was not corrected for the dependent planes of joint motion, as in a previous paper [17].…”
Section: Discussionmentioning
confidence: 80%
“…100 % of EMG equals the average of the two peak amplitude values during the two 5-s sessions of MVC. Third, EMG variables were calculated as RMS values within each 30-ms interval [10,15,16], averaged over 10 steps and normalized to peak MVC (%EMG). The different activity variables are described in Table 1.…”
Section: Data Reductionmentioning
confidence: 99%
“…According to Komi [9], the stretch-shortening cycle proceeds in three phases, namely pre-activity, eccentric lengthening and concentric contraction. Because of the eccentric lengthening a reactive and stronger contraction can follow, which allows the muscle to generate more strength in shorter time [9,10]. Stretch reflexes can be classified according to their latencies-i.e., reflex peaks-and are characterized by slow, mid and long latency responses and long latency succeeding responses in relation to an impact, e.g., the initial ground contact during running [10].…”
Section: Introductionmentioning
confidence: 99%
“…Integrated EMG (iEMG) parameters of lateral jumps were analyzed between -30 -0 ms, 0-30 ms, 30 -60 ms, 60-90 ms, and 90-120 ms epochs. All testing was performed in one session and electrodes were not removed, therefore normalization of iEMG and MAV was not necessary (Fleischmann et al 2010).…”
Section: Assessment Of Countermovement Jump and Lateral Jump Performancementioning
confidence: 99%
“…To the authors' knowledge, there is no study available that investigated the influence of unstable surfaces on activity of lower limb as well as trunk muscles during maximal jumping and cutting tasks. During cutting (i.e., lateral jumps) and jumping, it seems that EMG activity in lower limb muscles is preprogrammed during the preactivation phase (Dyhre-Poulsen et al, 1991;Avela et al, 1996) and affected by stretching loads (Avela et al 1996, Komi & Gollhofer 1997, Fleischmann et al, 2010Hoffrén et al, 2011) during the braking phase. In fact, it has been shown that muscle preactivation is related to the appearance and magnitude of spinal stretch reflexes during ground contact of drop jumps (Avela et al 1996).…”
Section: Introductionmentioning
confidence: 99%